Texts About Music: Reflections on the Relations Between the Different Communities Living in 19th Century Istanbul - Harun Korkmaz (Art-Sanat)
In the 18th century Istanbul, different congregational and ethnic groups started to come together in the public sphere. This created an environment of cultural transfer and exchange among the various congregations, that reached its climax at the beginning of the 19th century. Turkish classical music started to be written in Hamparsum notation which adapted the ancient note system of Armenian church music. The elements of the Rum Church and Profan Music met those of Turkish music. Several Jewish musicians emerged as masters who deeply affected the music in Istanbul. Gypsy composers entered the palace with their songs. In addition, the effect of western culture and music became more pronounced in the city. In the field of music print, developments included the writing down of Turkish music using Greek letters, Italian cantos with Arabic letters and Persian lyrics in Armenian letters. In this way, the cultures of the different ethnoreligious communities were intertwined with each other. The paper will present a portrayal of these interactions through an examination of written documents. To understand how Istanbul is nourished by both its own internal dynamics and the influences carried by the outside world, it will be tried toI will try to describe the sphere reflected in this article.